Discovery of PF-04457845: A Highly Potent, Orally Bioavailable, and Selective Urea FAAH Inhibitor - Johnson, Douglas S. (American Chemical Society, 2010)
[Image: see text] Fatty acid amide hydrolase (FAAH) is an integral membrane serine hydrolase that degrades the fatty acid amide family of signaling lipids, including the endocannabinoid anandamide. Genetic or pharmacological inactivation of FAAH leads to analgesic and anti-inflammatory phenotypes in rodents without showing the undesirable side effects observed with direct cannabinoid receptor agonists, indicating that FAAH may represent an attractive therapeutic target for the treatment of inflammatory pain and other nervous system disorders. Herein, we report the discovery and characterization of a highly efficacious and selective FAAH inhibitor PF-04457845 (23). Compound 23 inhibits FAAH by a covalent, irreversible mechanism involving carbamylation of the active-site serine nucleophile of FAAH with high in vitro potency (k(inact)/K(i) and IC(50) values of 40300 M(−1) s(−1) and 7.2 nM, respectively, for human FAAH). Compound 23 has exquisite selectivity for FAAH relative to other members of the serine hydrolase superfamily as demonstrated by competitive activity-based protein profiling. Oral administration of 23 at 0.1 mg/kg results in efficacy comparable to that of naproxen at 10 mg/kg in a rat model of inflammatory pain. Compound 23 is being evaluated in human clinical trials.